Research progress in low-cost preparation process of continuous fiber-reinforced silicon carbide ceramic matrix composites - SHANG Jianzhao; WU Xiaofei; CAO Yejie; LYU Yunlei; LI Jingxin; WANG Jing; DONG Ning; LIU Yongsheng (Cailiao gongcheng)
Continuous fiber-reinforced ceramic matrix composites have been widely used in aerospace， defense industry， emerging civilian，and other fields due to their excellent properties such as low density， high strength and high temperature resistance. However， most of the preparation processes of continuous fiber-reinforced ceramic matrix composites have problems such as high cost and long cycles， which limit the application and promotion of ceramic matrix composites. The development of a low-cost preparation process is the key to promoting the wide application of continuous fiber-reinforced ceramic matrix composites. In this paper， the preparation process of continuous fiber-reinforced ceramic matrix composites is briefly introduced， and the research status of low-cost processes such as reactive melt infiltration， nano infiltration and transient eutectoid， and slurry infiltration and hot pressing is summarized. The optimization of preparation process， microstructure and properties of composites is reviewed， and the future research direction of the low-cost preparation process is proposed， such as the preparation of ultra-high temperature ceramic interface by molten salt method and the preparation of porous matrix with uniform pore structure by reaction-induced phase separation， which can significantly improve the comprehensive properties of continuous fiber-reinforced ceramic matrix composites.